A new approach against Helicobacter pylori using plants and its constituents: A review study. (July 2022) - Sathianarayanan, Sankaran; Ammanath, Aparna Viswanathan; Biswas, Raja; B, Anita; Sukumaran, Sunitha; Venkidasamy, Baskar
Abstract: Helicobacter pylori is a Gram-negative, spiral-shaped bacillus that colonizes 50% of the world population and is considered a class 1 carcinogen by the World Health Organization. This pathogen is the most common cause of infection-related cancers. Apart from cancer, it also causes several gastric and extra gastric diseases. Eradication of H. pylori using antibiotics is a global challenge because of its drug resistance. Alternative treatment options are gaining more attention to tackle drug-resistant H. pylori infections. Several medicinal plants and their isolated compounds have been reported for their antimicrobial activity against H. pylori. The mechanism of action of many of these plant extracts and plant-derived compounds is different from that of conventional antibiotics. Therefore they are shown to be effective against drug-resistant strains of H. pylori. They act by inhibiting bacterial enzymes, adhesions with gastric mucosa, suppression of nuclear factor-κB and by inhibition of oxidative stress. Extracts from Pistacia lentiscus, Brassica oleracea, Glycyrrhiza glabra, Camellia sinensis, Cinnamomum cassia, Allium sativum and Nigella sativa plants and isolated phyto-compounds such as curcumin, resveratrol, quercetin, allicin and ellagic acid demonstrated antimicrobial activity against H. pylori under in vivo conditions. The plant extracts of Zingiber officinale, Glycyrrhiza glabra ; and phytochemical allicin and berberine when combined with standard treatment, result in a dramatic increase in H. pylori eradication. In this review, we highlighted the therapeutic efficacy of different plant extracts and isolated phyto compounds against H. pylori infection and described their role in tackling H. pylori resistance to antibiotics. Graphical abstract: Image 1 Highlights: Eradication of H. pylori using antibiotics is a global issue due to evolution of drug resistance. Therapeutic potential of various plant extracts in H. pylori treatment was discussed in detail. Mechanism of action of phytomaterials in inhibition of H. pylori . Synergic potential of antibiotics and phytocompounds in treatment of drug resistant H. pylori was discussed.